A fotografia e a pesquisa em história da educação: escolas paulistas na década de 1930 - Celeste Filho, Macioniro [UNESP] (My University, 2011)
In the Brazilian public archives,it is not unusual to find photographs recording the daily school educational institutions since at least the early twentieth century. The historian often has conceptual difficulties in dealing with the photographic documentation as a research source. The current workproposes to present the debate over the use of photographyas a privileged source for research on Education History. Photography can be an instrument of knowledge and information for observers awayfrom the place and time in which the images originated. Its contents have been tentativelyused in researchfor the Historyof Education. The methodologyof this studywill approach the ideas proposed byBoris Kossoyand Susan Sontag on photographyas a record of realityand its use in historical research. As interlocutors with the ideas of these three authors will be presented photographs of reports from the Regional O ffice of Education in the 1930s,preserved in the Public Archives of São Paulo. It is the purpose of this study to help researchers in History of Education in methodological reflection on the use of photographs as documentarysource of research.

Nos arquivos públicos brasileiros, não é raro deparar-se com fotografias registrando o cotidiano escolar de instituições educacionais desde, ao menos, o início do século XX. O historiador freqüentemente tem dificuldades conceituais em tratar a documentação fotográfica como fonte de pesquisa. O atual trabalho propõe apresentar o debate sobre o uso da fotografia como fonte privilegiada para a pesquisa em História da Educação A fotografia pode ser instrumento de conhecimento e informação para observadores afastados do lugar e da época em que as imagens tiveram origem. Seus conteúdos têm sido timidamente empregados em pesquisas de História da Educação. A metodologia deste trabalho abordará as idéias propostas por Boris Kossoy e Susan Sontag sobre a fotografia como registro da realidade e sua utilização na pesquisa histórica. Como interlocutoras às idéias destes três autores, serão apresentadas fotografias de relatórios de Delegacias Regionais de Ensino da década de 1930, preservadas no Arquivo Público do Estado de São Paulo. É objetivo deste trabalho auxiliar pesquisadores de História da Educação na reflexão metodológica do uso de fotografias como fonte documental de pesquisa.
Keywords: Historyof education; Photograph; Documentary sources; História da educação; Fotografia; Fontes documentais